Selection and characterization of single-stranded DNA aptamers against interleukin-5 - Mina Jamalvandi; Hossein Khanahmad; Shiva Irani; Sayad Bastaminezhad (Wolters Kluwer Medknow Publications, 2019)
Asthma as a chronic inflammatory disorder is associated with many cytokines like interleukin-5 (IL-5) which plays essential role in eosinophil differentiation and maturation. Accordingly, blockage of IL-5 using mepalizumab has been considered as a promising therapeutic approach for asthma. Despite the monocolonal antibody advantages, some restrictions provided an acceptable background for alternative agents like aptamers which could replace with antibodies. In the current study, aptamer isolation against IL-5 molecule was intended, according to the valuable benefits of aptamers over antibodies. HEK-293T/IL-5 cell was constructed to select aptamer using cell-systematic evolution of ligands by exponential enrichment (SELEX) method. Integration of the IL-5 fragment to genome of the HEK-293T was verified by polymerase chain reaction on the genomic DNA of the transfected cells. Moreover, IL-5 protein expression on the cell surface was confirmed using flow cytometry analysis. Then, cell SELEX was carried out in 12 rounds and isolated aptamers were evaluated by flow cytometry analysis. The selected clones were then sequenced and assessed for any possible secondary structure. The results of this study led to the selection of 19 different single-stranded DNA clones after 12 rounds of selection which were clustered to five groups based on common structural motifs. In conclusion, the findings revealed the isolation of IL-5-specific single-stranded DNA aptamers, which can further be substituted with mepolizumab.